ISTILAH KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA KOREA (SUATU ANALISIS KONTRASTIF) - ODE, ENDANG WATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research is an attempt to describe and analyse the kinship terms of English and Korean that are two different groups of language which have specific pattern of kinship terminologies. They have a special set terms to indicate the kinship relations. The aim of this research is to contrast the kinship terms in English and Korean by using Lado‟s concept. The concept of kinship terms is adapted from Murdock‟s book Social Structure (1949). The English data were collected from several relevant books, internet and previous thesis about kinship terms that have been done before, whereas the Korean data were collected from participants who are native Korean. The result of this research shows that kinship terms of English and Korean have similarities in terms of sex, generation, and decedence. The differences of both languages that English kinship terms does not contain  the semantic meaning, while the Korean does. In the generation, the English has four generations above and below ego, while Korean has two generations above and below ego.  Keywords: Kinship Terms, English and Korean, Contrastive Analysis